(3QSGdI aj GdMOhO GdWHjI hGdGUWdGM GdeJYdb HGdWHs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3GdWH Yde JYQa efg CMhGd HOf GdCfSGf ef LgI eG jUM hjRhd Yf GdUMI dJMaX MGUdg s
(3BNQgG (B:s
(3Cf jeJMf Pdc HCf jSNf GdYVh hjHQO Ch jLaa Ch jQWH dG HEaQGW Ch ZjQ Pdc eeG jhVM CeQg hdG NWQ ajg hgPG BNQ GdeSGFd GdWHjI GdeTJedI Ydi Led ef Yde GdWH s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs